2007
DOI: 10.1520/jai101101
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Building Construction—International Standards in Progress

Abstract: The development of ISO 15392 on general principles of sustainability in building construction took more time than expected. The most significant reason for this was the need to identify a common basis for the conceptual content of the document. With this basis now being identified, the work has taken up momentum and the general principles document presents principles to be considered when addressing the thematic field of sustainable development in relation to building and civil engineering. A key problem to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the performance of the components and the material must be assessed to ensure that the building meets the required performance level. Performance features of components, materials and arrangements cannot adequately and completely describe the performance of the structure (Trinius et al, 2005). The quality of the building depends on the interactions of various elements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the performance of the components and the material must be assessed to ensure that the building meets the required performance level. Performance features of components, materials and arrangements cannot adequately and completely describe the performance of the structure (Trinius et al, 2005). The quality of the building depends on the interactions of various elements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trinius et al stated that the standards play a significant role to achieve sustainable building certification or green building certification. But it is important to note that these standards may not be a solution to the problem [12]. Yu et al reported that the variable refrigerant flow (VRF) system consumes less energy than the variable air volume (VAV) system in an office building in China.…”
Section: Introductionmentioning
confidence: 99%
“…stated that the standards play a significant role to achieve sustainable building certification or green building certification. But it is important to note that these standards may not be a solution to the problem 12. Yu et al.…”
Section: Introductionmentioning
confidence: 99%